PEMANFAATAN POME SEBAGAI PUPUK ORGANIK PADA LAHAN PASCATAMBANG BATUBARA The Application of POME (Palm Oil Mill Effluent) as Organic Fertilizer for Ex-Coal Mine Soil - Puspita Laksmi Maharani; Prijanto Pamoengkas; Irdika Mansur (Jurnal Silvikultur Tropika, 2017)
Processing of palm oil generates enormous quantities of wastewater commonly called palm oil mill effluent (POME). The aim of the research was to evaluate the effect of POME as organic fertilizer on Melaleuca cajuputi seedling. The research was conducted at PT. Bukit Asam from November 2016 until March 2017. POME used was from PT. Bumi Sawindo Permai at Tanjung Enim, South Sumatera. POME from Fat pit, cooling pond, anaerob pond and maturity pond were applied to seedlings at nursery with different concentrations of POME Fat pit (625, 417, and 208 mL), Cooling pond (695, 463, dan 232 mL), Anaerob pond (738, 492, dan 246 mL), and Maturity pond (968, 645, dan 323 mL). The result showed that POME from Anaerob pond 246 mL increased the growth of M. cajuputi with plant high 47.35 cm and stem diameter 5.57 mm and total dry weight of CM (Calopogonium mucunoides) was 26.83 g.Key words: ex-coal mine soil, Melaleuca cajuputi, POME